DEVELOPMENT, FORMULATION AND EVALUATION OF MECLOFENAMATE FAST DISSOLVING TABLETS - Shakkarwal, Mahipal; Sharma, Dr. Mukesh; Garg, Dr. Ram; Soni, Shankar Lal; Paswan, Gopal Kumar; Naryan, Umansh (Journal of Biomedical and Pharmaceutical Research, 2021)
The demands for fast dissolving tablets have received ever increasing day by day during the last 10-15 years for the onset of action. In the present study, the effect of superdisintegrant was compared with synthetic super disintegrants and other conventional super disintegrants in the of fast dissolving tablet formulation of Meclofenamate.Meclofenamate is an antihypertensive drug and in case of hypertension immediate treatment is required so the proposed investigation is totally based to provide the suitable treatment for hypertension.In the present work 9 formulations of Fast dissolving tablets of Cilnidipine were prepared by using Synthesized Co-proceed was evaluated and compiles with the official standards, parameters and specifications.Various formulations were prepared using four different superdisintegrant namely- kyron T-304, sodium starch glycolate, cross carmelose sodium with three concentrations (2%, 4%, 6%) by direct compression method.The blend was evaluated for pre-compression parameters like Angle of repose , bulk density , tapped density , and then tablet  evaluated post-compression parameters like thickness , drug content , hardness , weight variation  , wetting time , friability , disintegration time , dissolution time, drug release study.Formulation A8 showed the lowest disintegration time and in-vitro dissolution studies recorded that formulation A8 showed 98.64% drug release at the end of 3 minutes.The best formulations were also found to be stable and optimized formulations were subjected to the stability studies as per ICH guideline and standards.